2000
DOI: 10.5271/sjweh.523
|View full text |Cite
|
Sign up to set email alerts
|

Maternal occupational risk factors for oral clefts

Abstract: Objectives This study investigated the role of maternal exposures at work during pregnancy in the occurrence of oral clefts. MethodsThe occupational exposures of 851 women (100 mothers of babies with oral clefts and 751 mothers of healthy referents) who worked during the first trimester of pregnancy were studied. All the women were part of a multicenter European case-referent study conducted using 6 congenital malfolmation registers between 1989 and 1992. In each center, the mother's occupational histoty, obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 39 publications
1
35
2
1
Order By: Relevance
“…Previous studies had indicated increased risks of hairdressers having an infant with a major malformation, such as oral clefts and hypospadias (21)(22)(23)(24). The pattern in the previous studies is not, however, consistent.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Previous studies had indicated increased risks of hairdressers having an infant with a major malformation, such as oral clefts and hypospadias (21)(22)(23)(24). The pattern in the previous studies is not, however, consistent.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition to these cohort studies, a few studies have indicated increased risks for more-specific malformations among hairdressers (23)(24)(25). The pattern is, however, inconclusive and a need for more studies exists.…”
mentioning
confidence: 99%
“…Some chemicals used by hairdressers, such as dibutyl phthalates (4), 2-nitro-p-phenylenediamine (5), and 4-nitro-o-phenyenediamine (5), have shown adverse reproductive effects in animal studies, but evidence from human studies is very limited (1,6). Some studies suggest that exposures in hairdressing salons may be related to menstrual disorders (7), spontaneous abortion (8)(9)(10), congenital malformations (9,11,12), small-for-gestational age (11,13), or delayed neurodevelopment in offspring (14), but others have not found any association (15)(16)(17).…”
mentioning
confidence: 99%
“…Earlier studies demonstrated that the alcohol consumption during pregnancy is associated with orofacial clefts [111,116]. Maternal alcohol consumption during the first trimester of pregnancy increased risk for isolated CP, but not for CLP [117]. Another study, found that maternal alcohol use during pregnancy among oral cleft cases was slightly more frequent than among controls [118].…”
Section: Environmental Factors Causing Cleftmentioning
confidence: 91%